Comparison of the actual costs during removal of concrete layer by high-speed water jets - Hela, Rudolf; Bodnárová, Lenka; Novotný, Miloslav; Sitek, Libor; Klich, Jiří; Wolf, Ivan; Foldyna, Josef (Journal of Business Economics and Management, 2012)
This paper describes the process of possible evaluation of costs of using high speed water jet technology for concrete removal methods. High speed water jet technology is a progressive technology of removing damaged concrete used in civil engineering since the 80’s of 20th century. It has been changing and developing since that time. But there is little information in literature devoted to the economic evaluation of this technology. Detailed economic analysis is still missing. This paper aims to compare comprehensively in economic terms the costs of removing concrete using the technology of both continuous oscillating and pulsating oscillating water jets. The research was realized in cooperation with research institutions and industrial companies and was supported by state budget of the Czech Republic and from the European Union. The scheme of cooperation of the University, research institutions, industrial companies and government follows the Triple helix model.